Engaging informal settlements as landscapes of place: reconceptualising urban communities in the struggle for in SITU upgrading. - Kornienko, Kristen (My University, 2014)
This study investigates the role of space and place in urban informal settlement upgrading. The key aim is a better understanding of the character and functionality of informal communities through their social processes. There is a large body of literature on the social, economic and spatial consequences of informal settlement’s ongoing role of housing the urban poor. This study uses an ethnographic approach to investigate the spaces and places which result from the need based social relations and political agency of the informal residents. This genre of need reflects Lefebvre’s description of the tangible and intangible necessities that contribute to individuals’ livelihood and well-being. The study explores the philosophical thinking around spatial production and the meaning of place. It builds on the works of Heidegger, Lefebvre, and Deleuze and Guattari who attribute value to everyday social process and its role in producing space. Deleuze and Guattariʼs relational language is used to articulate the fluidity with which informality engages formality through the rhythm, refrain, milieu and territorialisation of daily use, leading to a rethinking of boundary and edge. Critically, the study also draws on the historic and present elements of time as it relates to space for this group of thinkers. The time/space dynamics of hope lost through waiting for upgrading and hope gained through impatience, political agency and action, add layers of complexity to these spaces. Implied in the first dynamic is an acceptance of the status quo, passive inclusion into South Africaʼs democratic society through the eventual provision of housing. The second is an insurgent demand for socio-economic rights and societal transformation as guaranteed by the Constitution (Holston, 1998). The resultant qualitative data from two informal settlements in greater Johannesburg unravels the logic behind informal spatial production via relational connections which articulate space as a product of informal residents’ social actions. This spatial understanding suggests a shift away from current spatial models employed by the State in its formal provision of subsidised housing. At the same time, it strengthens informal communities’ role in the upgrading process by giving value to the social qualities of place in existing living environments.
Keywords: Housing--South Africa.; Squatter settlements--South Africa.